Characterization of the interaction between the HIV-1 Gag structural polyprotein and the cellular ribosomal protein L7 and its implication in viral nucleic acid remodeling. Issue 1 (December 2016) - Mekdad, Hala; Boutant, Emmanuel; Karnib, Hassan; Biedma, Marina; Sharma, Kamal; Malytska, Iuliia; Laumond, Géraldine; Roy, Marion; Réal, Eléonore; Paillart, Jean-Christophe; Moog, Christiane; Darlix, Jean; et al.
Abstract Background In HIV-1 infected cells, the integrated viral DNA is transcribed by the host cell machinery to generate the full length HIV-1 RNA (FL RNA) that serves as mRNA encoding for the Gag and GagPol precursors. Virion formation is orchestrated by Gag, and the current view is that a specific interaction between newly made Gag molecules and FL RNA initiates the process. This in turn would cause FL RNA dimerization by the NC domain of Gag (GagNC). However the RNA chaperoning activity of unprocessed Gag is low as compared to the mature NC protein. This prompted us to search for GagNC co-factors. Results Here we report that RPL7, a major ribosomal protein involved in translation regulation, is a partner of Gag via its interaction with the NC domain. This interaction is mediated by the NC zinc fingers and the N- and C-termini of RPL7, respectively, but seems independent of RNA binding, Gag oligomerization and its interaction with the plasma membrane. Interestingly, RPL7 is shown for the first time to exhibit a potent DNA/RNA chaperone activity higher than that of Gag. In addition, Gag and RPL7 can function in concert to drive rapid nucleic acid hybridization. Conclusions Our results show that GagNC interacts with the ribosomal protein RPL7 endowed with nucleic acid chaperone activity, favoring the notion that RPL7 could be a Gag helper chaperoning factor possibly contributing to the start of Gag assembly.